TERAPI AKTIVITAS KELOMPOK (TAK) STIMULASI PERSEPSI TERHADAP KEMAMPUAN PASIEN MENGONTROL HALUSINASI - Mone, Forbin; Antia, Antia (Indonesian Journal of Nursing Health Science, 2017)
AbstractHallucinations are the most frequent form of perceptual sensory impairment in the form of falsesounds, visions, tastes, touches and falsehoods. Group activity therapy (TAK) perceptual stimulation can be used to improve the patients ability to control hallucinations. This study aims to identify the effect of Â groupÂ activity therapy (TAK) perceptual stimulation on the patients ability to Â control hallucinations in psychiatric hospital Dr. Soeharto Heerdjan. This research method used pre- experiment Â with Â one Â group Â pre-post Â test Â design. Â A Â sample Â size Â of Â 28 Â respondentsÂ taken Â with probability sampling technique of simple random sampling. The result of hypothesis test of dependent sample t-test at significance level of 95% obtained Ï-value <Î± value, that is 0.000 means there is influence of group activity therapy (TAK) stimulation of perception to Â improvement of patients ability to control hallucination. Conclusions: There were differences in cognitive and psychomotor signs and symptoms before and after group therapy (TAK) stimulation of perception and it was suggested that the researcher could further develop the research to control the hallucination of the patient by giving other group activity (TAK) therapy such as group activity therapy (TAK) sensory stimulation.Â Keywords Â :Â Â groupÂ Â activityÂ Â therapyÂ Â (TAK),Â Â stimulationÂ Â ofÂ Â perception,Â Â abilityÂ Â toÂ Â control hallucinationsÂ AbstrakHalusinasi adalah bentuk peredaran sensorik persepsi yang paling sering dalam bentuk bunyi-bunyipalsu, penglihatan, selera, sentuhan dan kepalsuan. Terapi aktivitas kelompok (TAK) stimulasi perseptual dapat digunakan untuk meningkatkan kemampuan pasien untuk mengendalikan halusinasi. Penelitian ini bertujuan untuk mengidentifikasi pengaruh terapi aktivitas kelompok (TAK) stimulasi perseptual terhadap kemampuan pasien mengendalikan halusinasi di rumah sakit jiwa Dr. Soeharto Heerdjan. Metode penelitian ini menggunakan pra-eksperimen dengan satu kelompok desain pre-post test. Ukuran sampel 28 responden diambil dengan teknik probability sampling simple random sampling. Hasil uji hipotesis t-test sampel dependen pada taraf signifikansi 95% diperoleh nilai Ï- value Â <Î±, Â yaitu 0,000 berarti adaÂ pengaruh terapi aktivitas kelompok (TAK) stimulasi persepsi terhadap peningkatan kemampuan pasien untuk mengendalikan halusinasi. . Kesimpulan: Ada perbedaan tanda dan gejala kognitif dan psikomotorik sebelum dan sesudah terapi kelompok (TAK) stimulasi Â persepsi Â dan Â disarankanÂ bahwa Â peneliti Â dapat Â lebih Â mengembangkan penelitian Â untuk mengontrol halusinasi pasien dengan memberikan kegiatan kelompok lain (TAK) terapi seperti terapi aktivitas kelompok (TAK) stimulasi sensorik.Â Kata Â kunci: Â terapi Â aktivitas Â kelompok Â (TAK), Â stimulasi Â persepsi, Â kemampuan Â mengendalikan halusinasi